Performance of Multi-Canopy Rice Combinations Based on Tillering Capacity and Plant Architecture Across Seasons and Nitrogen Levels - Dwi Arizna Arofah; Willy Bayuardi Suwarno; Natasya Nafila; Ahmad Junaedi; Hajrial Aswidinnoor (Universitas Sebelas Maret, 2026)
The growing challenge of ensuring global food security encourages innovative approaches to rice cultivation. One novel innovation is the multi-canopy cropping system, involving planting 2 rice genotypes with different plant heights at close spacing. This study aimed to evaluate the effect of the tillering capacity of tall rice genotypes and the plant architecture of short genotypes on yield and agronomic traits in a multi-canopy system under different environmental conditions. The genetic materials were 24 combinations of multi-canopy rice genotypes belonging to 3 groups, namely T1-S1, T2-S2, and T3-S3, each consisting of 8 combinations. The T1, T2, T3 groups are the tall genotypes with different tillering ability, namely low, medium, and high; whereas the S1, S2, S3 groups are the short genotypes with different plant architecture, namely green revolution type, dwarf type, and stay green. These combinations were evaluated with 4 checks in 4 environments, i.e., 2 planting seasons and 2 nitrogen treatments. The combined analysis involving 3 factors (genotype combination, nitrogen, and season) was performed. The grain yield of all multi-canopy combinations was significantly higher than that of the check varieties in monoculture. Group T3-S3 had a significantly higher average total number of grains than the other groups. Selection based on Multi-trait Genotype-Ideotype Distance Index (MGIDI) at 20% pressure produced the desired selection differential for all selection traits. Four selected lines belonged to the T3-S3 group. The interaction between genotype combination and nitrogen fertilizer was significant for the number of total and productive tillers. This study provides insight for identifying suitable combinations of the tall and short genotypes in breeding multi-canopy rice varieties.